Utilization of the Canva Website as a Medium for Making Geography Comics to Improve Creative Thinking Skills in Class X Students of Sman 1 Rupat (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Technology that is increasingly developing and sophisticated, can make students also create without limits. The Canva website is one of the platforms that can be utilized by teachers and students in packaging learning, both inside and outside the classroom in a more fun and interesting way. In this study, the Canva website was used to create geography comics, especially hydrosphere material, as an effort to improve the creative thinking skills of class X students at SMAN 1 Rupat. This study used a quasi-experimental method with a quantitative approach involving experimental and control classes. The results of statistical calculations show that the use of the Canva website as a medium for making comics is quite effective in improving students' creative thinking skills. So that in the future it is highly recommended that educators/teachers use the Canva website with a longer time allocation for the habituation of students so that it can produce even better creative thinking skills and can make the Canva website more efficient and effective for learning media.